Spectrum of endoscopic gastric subepithelial lesions encountered on EUS-FNA: A single center experience - Poojan Agarwal; Pooja Bakshi; Kusum Verma; Vikas Singla; Anil Arora (Indian Journal of Pathology and Microbiology)
Background and Objectives: Endoscopic ultrasound guided fine needle aspiration (EUS-FNA) is a minimally invasive and reliable non-surgical technique for the diagnosis of gastrointestinal lesions. The present study aimed to evaluate the spectrum of lesions encountered in the gastric subepithelium on EUS-FNA at a tertiary care center. Materials and Methods: Archival data of all patients undergoing EUS-FNA for gastric submucosal lesions over a period of 5 years was retrieved. Patient demographics, clinical presentation, and EUS findings were recorded along with the FNA results. Results: A total of 78 EUS-FNA samples were analyzed. Material was adequate in 62 cases (79.48%) and inadequate in 16 cases (12.82%) patients due to scant cellularity. Of the adequate samples, 34 (43.5%) were reported as neoplastic while 20 (25.64%) were non-neoplastic, and 8 (10.25%) were reported as suspicious of a neoplasm. In the neoplastic category, the predominant diagnosis was of spindle cell neoplasm comprising gastrointestinal stromal tumor (13), benign neural tumor (03), leiomyoma (02), and spindle cell tumors (03). The latter could not be categorized further due to a lack of IHC material. The next common diagnosis was adenocarcinoma (06) followed by neuroendocrine tumor (02) and poorly differentiated carcinoma (01). The non-neoplastic lesions included non-specific pathology (15), inflammatory lesions (08), and one case each of tuberculosis, pancreatic rest, and Brunner gland hamartoma. Cell blocks for ancillary testing were available in 54 cases (65.23%) and follow-up was available in 42 cases (53.84%). Conclusion: EUS-FNA is a good modality for the diagnosis of gastric submucosal lesions with a high diagnostic yield.